2010
DOI: 10.1007/s00018-010-0587-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological implications of preformed mast cell mediators

Abstract: Mast cells store an impressive array of preformed compounds (mediators) in their secretory granules. When mast cells degranulate, these are released and have a profound impact on any condition in which mast cell degranulation occurs. The preformed mast cell mediators include well-known substances such as histamine, proteoglycans, proteases, and preformed cytokines, as well as several recently identified compounds. Mast cells have recently been implicated in a large number of novel pathological settings in addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
97
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 113 publications
0
97
0
1
Order By: Relevance
“…histamine, serotonin), preformed cytokines (e.g. TNF), and anionic proteoglycans of serglycin type and various MC-specific proteases, the latter including tryptases, chymases, and carboxypeptidase A3 (2)(3)(4). Previous studies have shown that serglycin proteoglycan has a key regulatory role in maintaining the homeostasis of the secretory granules by forming complexes with the various granule proteases and bioactive amines, thereby promoting their storage within granules (5,6).…”
Section: Mast Cells (Mcs)mentioning
confidence: 99%
“…histamine, serotonin), preformed cytokines (e.g. TNF), and anionic proteoglycans of serglycin type and various MC-specific proteases, the latter including tryptases, chymases, and carboxypeptidase A3 (2)(3)(4). Previous studies have shown that serglycin proteoglycan has a key regulatory role in maintaining the homeostasis of the secretory granules by forming complexes with the various granule proteases and bioactive amines, thereby promoting their storage within granules (5,6).…”
Section: Mast Cells (Mcs)mentioning
confidence: 99%
“…When MCs are activated they may degranulate and thereby release a number of preformed compounds from their secretory granules, including bioactive amines, cytokines, proteoglycans and various MC-specific proteases, the latter encompassing chymases, tryptases and carboxypeptidase A3 2,3 . Activated MCs may also respond by de novo synthesis of additional pro-inflammatory compounds 4 .…”
Section: Introductionmentioning
confidence: 99%
“…MCs operate through a wide variety of bioactive mediators that they release in response to activation by, for example, Fc ɛ RI crosslinking (Lundequist and Pejler , 2011 ). Proteases are stored in exceedingly high amounts in the secretory granules of MCs, and they are released as fully active enzymes upon degranulation (Pejler et al , 2007 ).…”
Section: Introductionmentioning
confidence: 99%